Possible association between anti-Ro antibodies and myocarditis or cardiac conduction defects in adults with systemic lupus erythematosus. Issue 8 (August 1990) - Logar, D; Kveder, T; Rozman, B; Dobovisek, J
Abstract : In view of the association of congenital heart block with maternal antibody to cellular antigen Ro (SSA), and one report linking anti-Ro with myocarditis in a patient with myositis an association between anti-Ro antibodies and cardiac disease was sought in adults with systemic lupus erythematosus (SLE). Among 67 patients with SLE, of whom 36 were anti-Ro positive, a significantly higher prevalence of myocarditis and conduction defects was found in the anti-Ro positive group (eight of 36) than in those who were anti-Ro negative (one of 31) and healthy controls (one of 50). Of the 36 anti-Ro positive patients with SLE, three had symptoms diagnostic of myocarditis, and an electrocardiogram showed first degree atrioventricular block and unifascicular block in three cases (including one with myocarditis), right bundle branch block alone (two cases), and first degree atrioventricular block alone (one case). Complete atrioventricular block was not seen. In the anti-Ro negative group there was no myocarditis and only one case of conduction defect (right bundle branch block). Among healthy controls only one of 50 had first degree atrioventricular block. It is concluded that myocarditis and conduction defects are reasonably common in adults with SLE and are associated with anti-Ro antibodies.